Visualização e valorização da paisagem a partir de geogame - Ítalo Sousa de Sena (2019)
Landscape is understood as the elements present in space that are perceptible to our senses, and can assume specific values according to the perspective of observation or functions associated to it. In the discovery of the landscapes of Minas Gerais, the relief and its physiographic features served as geographical landmarks, guiding the occupation of the territory and exploitation of natural resources, which produced a cultural landscape strongly linked to geodiverse aspects of the landscape along more than three centuries. These aspects present intrinsic values, related to the processes that provide environmental services that maintain life on Earth, as well as values related to the construction of identity with the landscape, generating identity relations constituting the cultural character expressed in space from anthropic activities. These relationships are built from the perception of the landscape component elements, constituting the mental maps, which guide the decision making about the action on the environment. Virtual environments produced for digital games have potential for the representation of geodiverse elements of the landscape, considering the various processes present in geosystems. In this perspective, Minecraft was used as a tool for spatial representation and visualization of the geodiverse landscape of Serra de Ouro Preto, associated with a game-design as a motivator for the exploration of the territory and interpretation of landscape values. The research started from the hypothesis that the virtual environment representing the landscape, linked to an exploratory game, is capable of favoring the visualization and abstraction of the values related to geosystemic services, providing bases for the construction of a geodiverse image of the Serra de Ouro Preto cultural landscape, considering the elements that constitute the spatial configuration of the city. As a way of investigating the question, the research developed from the creation of a geogame using the digital game Minecraft, considering places of interest for geodiversity present in the Serra de Ouro Preto. The thesis presents as contribution the construction method of GeoMinasCraft and the evaluation of results, which allowed the measurement of the interaction of digital natives with the virtual environment of the game and the evaluation of the development of spatial awareness and general aspects of local geodiversity.